Anti-Bullying Goes to School: Program Edukasi, Intervensi Dini, dan Literasi Bahasa Inggris di SDN 03 Popayato Barat - Ayuba, Hasan; Sintiawati, Rini; Ajun, Rinto S.; Sumenge, Firanda; Pakaya, Dian; Mahmud, Iswanda; Lapungu, Siskawati; Amran, Julman; Abdul Haris, Waraqotul Jannah; Udjaili, Oktaviani (LP2M IAIN Sultan Amai Gorontalo, 2025)
This community service program aimed to provide early education and intervention for students at SDN 03 Desa Persatuan Poyato Barat regarding the dangers of bullying and the importance of building a safe and inclusive school environment. In addition, the program introduced basic English literacy through thematic vocabulary related to emotions, social interaction, and positive values. The three-day activity involved educational socialization, group discussions, role-playing simulations, and contextual English language learning. More than 60 students from grades IV, V, and VI actively participated in all sessions. The results indicated an increased understanding of different forms of bullying, improved empathy, and the use of simple English expressions in social contexts. This program demonstrates that a participatory approach combining character education and English literacy is effective in fostering social awareness and basic language skills simultaneously.